A port-based evaluation framework of trade facilitation policies: Case of Shenzhen and Hong Kong. Issue 2 (June 2018) - Cheng, Michael C.B.; Wang, Donggen; Wang, James J.
Highlights: Port-level trade facilitation policies might vary between different hub ports of a country. Establishment of free trade zones (FTZ) in port cities of developing countries further differentiates trade formalities and supporting services of the related hub ports. Regular economic publications such as Global Competitiveness Report or Doing Business, fail to accurately capture the effects of port-oriented trade facilitation programmes. The evaluation framework proposed by this article effectively examines port-level trade facilitation policies from supply chain perspectives and assesses their impacts on competitiveness of the related gateway. Abstract: In recent years, trade facilitation becomes more complicated as related policies vary from state to port level, while at the same time free trade zones are also developing. Global indicators that have been commonly applied to monitor state-level trade facilitation policies fail to capture effects of similar measures at hub ports. This study develops an evaluation framework that adopts supply chain dimensions to examine the effects of port-level trade facilitation policies. Port of Shenzhen and Hong Kong are investigated by such framework to reveal the breadth and depth of trade facilitation programmes. Outcome of this research not only explains the effects of hub-port oriented trade facilitation measures, such framework could also facilitate the formulation, implementation, and review of trade facilitation policies.